The Fourth Industrial Revolution (Industry 4.0): A Social Innovation Perspective - Morrar, Rabeh; Arman, Husam; Mousa, Saeed (Technology Innovation Management Review, 2017)
The rapid pace of technological developments played a key role in the previous industrial revolutions. However, the fourth industrial revolution (Industry 4.0) and its embedded technology diffusion progress is expected to grow exponentially in terms of technical change and socioeconomic impact. Therefore, coping with such transformation require a holistic approach that encompasses innovative and sustainable system solutions and not just technological ones. In this article, we propose a framework that can facilitate the interaction between technological and social innovation to continuously come up with proactive, and hence timely, sustainable strategies. These strategies can leverage economic rewards, enrich society at large, and protect the environment. The new forthcoming opportunities that will be generated through the next industrial wave are gigantic at all levels. However, the readiness for such revolutionary conversion require coupling the forces of technological innovation and social innovation under the sustainability umbrella.
Place: Ottawa Publisher: Talent First Network
Keywords: Canada; Internet des objets; Libre accès

The Fourth Industrial Revolution (Industry 4.0): A Social Innovation Perspective - Morrar, Rabeh; Arman, Husam; Mousa, Saeed (Technology Innovation Management Review, 2017)
The rapid pace of technological developments played a key role in the previous industrial revolutions. However, the fourth industrial revolution (Industry 4.0) and its embedded technology diffusion progress is expected to grow exponentially in terms of technical change and socioeconomic impact. Therefore, coping with such transformation require a holistic approach that encompasses innovative and sustainable system solutions and not just technological ones. In this article, we propose a framework that can facilitate the interaction between technological and social innovation to continuously come up with proactive, and hence timely, sustainable strategies. These strategies can leverage economic rewards, enrich society at large, and protect the environment. The new forthcoming opportunities that will be generated through the next industrial wave are gigantic at all levels. However, the readiness for such revolutionary conversion require coupling the forces of technological innovation and social innovation under the sustainability umbrella.
Number: 11 Place: Ottawa Publisher: Talent First Network
Keywords: Canada; Internet des objets; Libre accès